Person-centred health outcomes in the routine care for people with progressive pulmonary fibrosis: the COCOS-IPF project’s European survey on healthcare professionals’ views and practices - Vivien Somogyi; Anouk Delameillieure; Silja Schenk; Liesbet Van Bulck; Sofie Breuls; Nazli Üçkuyu; Zehra Nur Töreyin; Nikola Stenzel; Nesrin Moğulkoç; Wim Wuyts; Steve Jones; Liam Galvin; et al. (Respiratory Research)
Abstract Background Idiopathic pulmonary fibrosis (IPF) and progressive pulmonary fibrosis (PPF) are interstitial lung diseases (ILD) that carry a high burden and mortality. IPF/PPF experts and patients call for standardized care, outcome harmonization and holistic management in these complex and devastating diseases, with a focus on person-centeredness. In this cross-sectional international survey study, we aimed to gather information on the person-centred health outcomes European healthcare professionals (HCPs) already use or deem important for use in routine care for IPF/PPF. This work is part of the COCOS-IPF project on developing a Core Outcome Set (COS) for and with patients with IPF/PPF. Methods With the input of IPF/PPF experts, psychologists and patients, we developed an online survey for European multidisciplinary HCPs with IPF/PPF expertise. The survey was programmed in QualtricsXM, piloted and distributed via the networks of the COCOS-IPF consortium. We used content analysis to create an overall list of outcome domains mentioned in the survey, classified these according to the COMET (Core Outcome Measures in Effectiveness Trials) taxonomy and calculated the frequency of all outcomes mentioned. Results A total of 149 experts, mainly pulmonologists (n = 120, 81%) working in ILD expert centres, from 31 European countries participated. Of the 40 different outcome domains mentioned, the majority referred to `physiological/clinical` (n = 773, 81%) and `life impact` (n = 138, 14%) outcome domains. Of these, `lung function’ (n = 280, 29%), ‘exercise capacity’ (n = 123, 13%) and `quality of life` (n = 103, 11%) were reported as most frequently used person-centred health outcomes. Survey respondents deemed the same three outcome domains the most important for use in the routine clinical IPF/PPF care, supplemented by chest symptoms. Pulmonologists reported mainly about routine use of `lung function` (n = 252, 26%), while allied HCPs put more focus on outcomes related to physical condition and whole body status. Conclusions HCPs have identified 40 different outcomes domains in a European multidisciplinary survey on person-centred health outcomes in IPF/PPF. Lung function, exercise capacity, quality of life and chest symptoms were rated as the most relevant health outcomes to be assessed routinely in clinical care. These insights can help to support the development of a COS for IPF/PPF clinical care.